Correlation between 24-hour Urinary Total Protein Excretion and Single Urinary Protein Creatinine ratio in the Diagnosis of Childhood Nephrotic Syndrome : Study in a Tertiary Level Hospital - Anowar, Asma Bint; Sarker, Nihar Ranjan; Md Mahamuduzzaman, Abu Shoyeb; Shome, Amit; Morshed, Sumon Shahrior; Parvin, Jobaida (Journal of Shaheed Suhrawardy Medical College, 2023)
Introduction:Protein excretion varies in the course of the day, for this reason 24-hours urinary total protein excretion has been considered as the classic reference method for protein determination in nephotic syndrome. As the collection of urine for 24 hours is tedious and errors may occur during the process, so the protein:creatinine ratio was developed as a diagnostic alterative for Nephrotic syndrome.The main aim of this study is to determine the correlation between 24-hour urinary total protein excretion and single urinary protein creatinine ratio in childhood Nephrotic syndrome. Methods: This cross-sectional study was conducted in the department of Paediatrics,Shaheed Suhrawardy Medical College & Hospital from June 2018 to May 2019. After taking valid consent total 60 cases of Nephrotic syndrome were selected purposively according to inclusion and exclusion criteria. Here we tried to determine the correlation between 24-hour urinary total protein excretion and single urinary protein creatinine ratio in the diagnosis of childhood Nephrotic syndrome by measuring the spot urinary protein creatinine ratio and the 24 hours urinary total protein excretion of the patients. Results : Among total 60(N) children of Nephrotic syndrome 42 (70%) patients were male and 18 (30%) patients were female with M:F = 2.16:1.The mean age was 4.57 ± 2.01SD years. Most of the patients were presented with some associated diseases like urinary tract infection (30%), upper respiratory tract infection (28.3%), viral illness(8.3%), atopic dermatitis(3.3%) and nonspecific illnesses(30%). The main physical findings were only puffy face(100%), with ascites (86.6%) and swelling of genitalia (38.3%).The mean 24 hours urinary total protein excretion was 3114.45 ± 1627.89 mg/24 hours and spot urinary protein creatinine ratio was 5.57 ± 3.13 SD. There was a very significant correlation between 24 hour total urinary protein excretion and spot urinary protein creatinine ratio. The sensitivity of the study was 80.49 – 100% and specificity of 91.78 - 100% at £2000 mg /sqm body surface area/ day protein excretion. The p value was .002 with correlation coefficient was 0.39. Conclusion: The protein creatinine ratio of a random urine sample might be used as an alternative method for the diagnosis of Nephrotic syndrome in children in view of the obvious advantages in terms of cost, time and patient convenience. J Shaheed Suhrawardy Med Coll 2021; 13(2): 137-142